Os professores aposentados da rede estadual de educação do Paraná, do município de Sengés – PR: analogias entre aposentadoria, trabalho e envelhecimento - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This thesis was developed based on the following guiding question: What are the relationships between retirement, work and aging for retired teachers from the state education network of Paraná, in the municipality of Sengés-PR? The general objective of the research was to analyze the relationships between retirement, work and aging for retired teachers from the state education network of Paraná, in the municipality of Sengés-PR. The argument of this thesis is to prove, based on the production and analysis of data, that retirement is not related to the onset of old age. Thus, the thesis we defend is that retirement does not represent the initial milestone of old age, as it is possible to create new life projects after breaking away from the world of work.This is a qualitative research, whose work methodology used the methodological procedures of oral history, semi-structured interviews (collection of five oral statements) and participant observation, as well as a bibliographical review on the historical aspects of the teaching profession. In this way, an analysis of the relationships between retirement, work and aging was carried out for retired teachers from the state education network of Paraná, in the municipality of Sengés-PR, seeking to understand aspects of the complexity of the teaching profession in Brazil; identify the meaning of retirement, work and aging for retired teachers from the state education network in the city of Sengés-PR, verifying the implications of retirement for these subjects in the construction of new life projects.To achieve these objectives, the research was structured and organized using Oral History as a theoretical-methodological framework Goldenberg (2002) and Queiroz (1991), using Oliveira (2011; 2012), Santos(1990) and Dartora (2009) as a theoretical framework. in reflections on retirement and its relationship with work and old age; Debert (1999) and Siqueira (2001) in their reflections on the agingprocess; Gatti (2010) and Silva and Catani (2011) in understanding the complexity of the teaching profession in Brazil because there is not just one, but different teaching cultures in Brazil.Among the main results of the thesis, it is highlighted that the participants in this research are part of a peculiar group within the set of Brazilian teachers who work in basic education (final years of elementary and secondary education) and even within the reality of the state network of education in the state of Paraná, from which they retired. Their entry was due to political recommendation, since at the time they joined (1960s) there was still no requirement for public examinations, as well as there were few teachers with degrees.The teaching profession, regardless of the age group or the historical moment in which one works or has worked, is permeated by several dilemmas, thus, the participating teachers experienced different phases of the teacher's career, from entering the career to the disinvestment phase. The study showed that the participants have a positive conception of retirement and work, experiencing it as a moment of fulfillment, of freedom achieved after several years dedicated to professional activities, in this case, teaching. It was also observed that there is an intrinsic relationship between retirement, work and aging, since work was situated as central in their lives and through this they gained the benefit of retirement, which is seen as a merit, a period of freedom which allowed them to build new life projects. Finally, it is expected that this work, in addition to encouraging new research on retirement and old age in Brazil, will contribute to expanding knowledge in the area of the History of Brazilian Education.
Keywords: Aposentadoria; Trabalho; Velhice; Envelhecimento; Professores; Retirement; Work; Old age; Aging; Teachers; CNPQ::CIENCIAS HUMANAS::EDUCACAO